2018
DOI: 10.1111/jgs.15603
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Medication Burden and Risk of Recurrent Serious Falls and Hip Fractures in Veterans Affairs Nursing Home Residents

Abstract: Objectives To examine the association between central nervous system (CNS) medication dosage burden and risk of serious falls, including hip fractures, in individuals with a history of a recent fall. Design Nested case–control study. Setting Veterans Health Administration (VHA) Community Living Centers (CLCs). Participants CLC residents aged 65 and older with a history of a fall or hip fracture in the year before a CLC admission between July 1, 2005, and June 30, 2009. Each case (n = 316) was matched to four c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…Individual variables representing markers of poor prognosis were constructed using MDS items including cancer diagnosis, swallowing problems, intravenous (IV) tube feeding, mechanical diet, poor appetite, recent weight loss, shortness of breath, recent changes in cognitive status, dehydration, renal failure, and pain. Having a fall in the 180 days before admission was identified using the MDS fall history item and/or meeting established claims‐based criteria for serious fall injuries . Behavioral problems were assessed using the MDS Aggressive Behavior Scale .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual variables representing markers of poor prognosis were constructed using MDS items including cancer diagnosis, swallowing problems, intravenous (IV) tube feeding, mechanical diet, poor appetite, recent weight loss, shortness of breath, recent changes in cognitive status, dehydration, renal failure, and pain. Having a fall in the 180 days before admission was identified using the MDS fall history item and/or meeting established claims‐based criteria for serious fall injuries . Behavioral problems were assessed using the MDS Aggressive Behavior Scale .…”
Section: Methodsmentioning
confidence: 99%
“…Having a fall in the 180 days before admission was identified using the MDS fall history item and/or meeting established claims-based criteria for serious fall injuries. [36][37][38] Behavioral problems were assessed using the MDS Aggressive Behavior Scale. 39 Dependency in activities of daily living (ADLs) was assessed using the ADL short form.…”
Section: Predictors Of Discontinuationmentioning
confidence: 99%
“…The main reason for the increase was that patients taking opioids were prone to vertigo and falls that can lead to fractures. In addition, Aspinall's et al [6] study showed that patients receiving opioid therapy had an increased risk of falls, and the accompanying final outcomes were fractures [6]. Schwarzer et al's [8] study also suggested that when opioid use was considered, the risk of fractures increased [8].…”
Section: Plos Onementioning
confidence: 99%
“…In addition, studies have shown that opioid-induced fractures are associated with time of use [5] and are also associated with the use of opioids [6]. Opioids have been linked to the occurrence of fractures [2,3,[7][8][9][10][11], and although the use of opioids has been reported to increase the risk of fractures, the trend of using opioids continues to increase [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have shown that opioid-induced fractures are associated with time of use [5] and are also associated with the use of opioids [6]. Opioids have been linked to the occurrence of fractures [2,3,711], and although the use of opioids has been reported to increase the risk of fractures, the trend of using opioids continues to increase [12].…”
Section: Introductionmentioning
confidence: 99%